Journeys through babudom and netaland : governance in India - Subramanian, T. S. R. (New Delhi : Rupa & Co., 2004)
Service memoirs of T.S.R. Subramanian, former cabinet secretary, government of India; includes autobiographical references.
Includes index.
Keywords: Subramanian, T. S. R; Civil service -- India -- Biography; Government executives -- India -- Biography